What Are the Differences Between the Perceived Unsolicited Social Support Provided by Offline Communities and Non-Support-Based Virtual Communities - Scadden, Edie (Auckland University of Technology, 2013)
There has been much academic debate since the advent of the internet as to the merits or shortcomings of the virtual community (Bell, 2001; Horrigan & Rainie, 2001; Rheingold, 1993/2000; Wellman, 2001a; Wilbur, 2000). I will demonstrate that, to date, very few researchers have touched on the social support aspect of virtual communities, although limited research has been undertaken around the support provided by non-support-based virtual communities. There has been no research conducted that compares this with support provided in offline communities. This research involved interviewing participants from a range of hobby communities, to compare the levels of social support and advice provided by their various communities, both virtual and physical. There has been discussion as to whether or not the arrival of the internet heralded the demise of the community. Putnam stated that by 1996 the internet was being used by 10% of adult Americans, however the “nationwide decline in social connectedness and civic engagement had been under way for at least a quarter of a century” (Putnam, 2000, p. 170). Researchers have indicated that there is a need for more in-depth research comparing virtual with physical communities, for instance Dutta-Bergman suggested that those who communicate with their local communities when in need, also communicate with their online communities for social support, and vice versa (Dutta-Bergman, 2006, p. 482), and Piselli proposed that online communication operates in conjunction with other aspects of everyday life and proposed that research is needed into how these various methods of interaction dominate, coincide, or coalesce in their various environments (Piselli, 2007, p. 875). Putnam concluded that online communication would ultimately supplement, rather than replace, the physical community (Putnam, 2000, p. 179). This research investigated the accuracy of Putnam’s hypothesis, by looking at the social support provided by the participants’ many communities (local neighbourhood, sports team or club, online gaming community, church, work colleagues, social networking community etc) and examining which of these they would most likely communicate with about important emotional, financial, health, bereavement or career problems and from which of these they would expect to receive support and advice.
Keywords: Social support; Virtual communities; Offline communities; Social media; Grounded theory